2021
DOI: 10.1172/jci144703
|View full text |Cite
|
Sign up to set email alerts
|

Gluconeogenic enzyme PCK1 deficiency promotes CHK2 O-GlcNAcylation and hepatocellular carcinoma growth upon glucose deprivation

Abstract: Although cancer cells are frequently faced with nutrient-and oxygen-poor microenvironment, elevated hexosamine-biosynthesis pathway (HBP) activity and protein O-GlcNAcylation (a nutrient sensor) contribute to rapid growth of tumor and are emerging hallmarks of cancer. Inhibiting O-GlcNAcylation could be a promising anti-cancer strategy. The gluconeogenic enzymes phosphoenolpyruvate carboxykinase 1 (PCK1) was downregulated in hepatocellular carcinoma (HCC). However, little is known about the potential role of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 64 publications
3
44
2
Order By: Relevance
“…Huh7 human HCC cells carrying a PCK1 S90A mutation, which abolishes the activity of phosphorylating INSIGs, fails to grow after in vivo xenografting [ 33 ]. Except for compartment-specific activity, this may also depend on glucose availability, since neither PCK1 overexpression nor depletion promotes HCC growth under high-glucose conditions [ 106 ]. Although much remains to be explored, these studies, in concert, demonstrate the metabolic vulnerability of cancer cells and indicate that both PCK1 and PCK2 may be promising therapeutic targets in clinic practice.…”
Section: Pck and Clinical Relevancementioning
confidence: 99%
“…Huh7 human HCC cells carrying a PCK1 S90A mutation, which abolishes the activity of phosphorylating INSIGs, fails to grow after in vivo xenografting [ 33 ]. Except for compartment-specific activity, this may also depend on glucose availability, since neither PCK1 overexpression nor depletion promotes HCC growth under high-glucose conditions [ 106 ]. Although much remains to be explored, these studies, in concert, demonstrate the metabolic vulnerability of cancer cells and indicate that both PCK1 and PCK2 may be promising therapeutic targets in clinic practice.…”
Section: Pck and Clinical Relevancementioning
confidence: 99%
“…Published studies have suggested that cellular O-glycosylation level is highly associated with the activities of OGT or OGA and the level of substrate UDP-GlcNAc (85)(86)(87)(88). However, the direct and detailed role of pyrimidine synthesis in the regulation of Oglycosylation is not well established.…”
Section: Dysfunction Of Pyrimidine Metabolism In Cancersmentioning
confidence: 99%
“…Nevertheless, whether the PCK1 protein kinase activity plays an essential role in this context remains unclear. In human hepatocellular carcinoma where PCK1 is markedly depleted, accumulation of the PCK1 substrate oxaloacetate activates checkpoint kinase 2 to promote cancer cell proliferation, reinforcing the functional importance of PCK1 metabolic activity (Xiang et al, 2021).…”
Section: Gluconeogenesismentioning
confidence: 91%